VD_FINDINFO Décision / 2015 / 218 vom 12. März 2015 - VD Tribunal cantonal (2015)
ORDONNANCE DE CONDAMNATION, OPPOSITION TARDIVE, DÉLAI DE RECOURS | 356 al. 2 CPP (CH), 393 al. 1 let. b CPP (CH), 85 CPP (CH)